0
votes
0answers
66 views

Fibonacci sequence: Prove the formula $f_{2n+1}=f_{n+1}^2 + f_n^2$ [duplicate]

I can't seem to figure out this proof. I'm using weak induction and always get stuck during the inductive step. Prove for n > 0: $$f_{2n+1} = f_{n+1}^2 + f_n^2$$
3
votes
3answers
50 views

When do you need to prove more than 1 base case in the Fibonacci problem?

I was trying to prove that if $F_n = F_{n-1} + F_{n-2}$ and $F_1 = 1$ and $F_2 = 1$, then the following proposition $P(n)$ was true $\forall n : \sum^n_{i=1}F_i=F_{n+2} - 1$ The issue I have with the ...
0
votes
2answers
46 views

Proof of the inequality $F_i<(5/3)^i$ for the Fibonacci numbers

The example states: As an example, we prove that the Fibonacci numbers, F0 = 1, F1 = 1, F2 = 2, F3 = 3, F4 = 5,..., Fi = Fi - 1 + Fi - 2, satisfy Fi < (5/3)i, for all i >= 1. To do this, we ...
3
votes
3answers
85 views

Proof by induction: $n$th Fibonacci number is at most $ 2^n$

I'm trying to find the proof by induction of the following claim: For all $n\in\mathbb N$, $\operatorname{fibonacci}(n) \le 2^n$ My Proof: Base case: $n = 1$ $\operatorname{fibonacci}(1) \le 2^ 1$ ...
2
votes
0answers
77 views

Can I use the equality $\phi^2=\phi+1$ without proving it?

I am looking at the following exercise: $$\text{ Show with induction,that the } i^{th} \text{ number Fibonacci satisfies the equality: } $$ $$F_i=\frac{\phi^i-\hat{\phi}^i}{\sqrt{5}}$$ where $\phi$ ...
0
votes
1answer
43 views

Base case in the Binet formula (Proof by strong induction)

I don't understand why the author says that the inductive formula does not apply until $u_3$. The formula does not depend on other terms in the Fibonacci sequence, so I thought I could just prove it ...
1
vote
4answers
88 views

Determine which Fibonacci numbers are even

(a) Determine which Fibonacci numbers are even. Use a form of mathematical induction to prove your conjecture. (b) Determine which Fibonacci numbers are divisible by 3. Use a form of mathematical ...
0
votes
1answer
25 views

Factoring for Strong Induction for Fibonacci Sequence

Fibonacci: prove the following theorem: define the Fibonacci sequence $\left\{ a_n\right\}_{n=0}^{\infty}$ by $a_0=a_1=1$ and for integers $k>1$, $a_k=a_{k-1}+a_{k-2}$. Then, for each integer $n$, ...
2
votes
1answer
87 views

Help with induction proof for formula connecting Pascal's Triangle with Fibonacci Numbers

I am in the middle of writing my own math's paper on the topic of Pascal's Triangle. During the investigation I have came up with a formula for counting elements of Fibonacci Sequence using the ...
0
votes
1answer
45 views

Fibonacci Proof with Induction [duplicate]

$$f(n) = \left\{\begin{matrix} 0 & n=1\\ 1 & n=2\\ f_{n-1} + f_{n-2} & n\geqslant 2\end{matrix}\right.$$ How can I prove by induction that $$f_{n} \geq \left ( 1.5 \right )^{n-1}$$ ...
2
votes
2answers
61 views

Fibonacci Proof Using Induction

$$f(n) = \left\{\begin{matrix} 0 & n=1\\ 1 & n=2\\ f_{n-1} + f_{n-2} & n\geqslant 2\end{matrix}\right.$$ How can I prove by induction that $$f_{n} \leq \left ( \frac{1+\sqrt{5}}{2} ...
2
votes
1answer
62 views

Fibonacci proof by induction

I have fibonacci numbers defined as such: $$ f(n) = f(n-1) + f(n-2)$$with$$ f(0) = 0 $$$$f(1) = 1$$ I have to prove that $$ F(n) \geq 1.5^{n-1}, n \geq 6$$ Base Case: $$ f(6) = 8 \geq (1.5)^5 ...
6
votes
4answers
87 views

Proof by induction that if $n \in \mathbb N$ then it can be written as sum of different Fibonacci numbers

Proof that every natural number $n\in \mathbb N$, can be written as the sum of different Fibonacci numbers between $F_2,F_3,\ldots,F_k,\ldots$. For example: $32 = 21 + 8+3 = F_8+F_6+F_4$ Research ...
2
votes
2answers
58 views

Proof by induction of a Fibonaci relation [duplicate]

We know: $F_0 = 0$ $F_1 = 1$ $F_i = F_{i-1} + F_{i-2}$ for $i \geq 2$ Prove by induction: $F_i = \dfrac{\phi^i-{\phi^{*}}^i}{\sqrt{5}}$ where $\phi = (1+\sqrt{5}) / 2$ and $\phi = (1-\sqrt{5}) / ...
0
votes
1answer
168 views

Fibonacci proof by Strong Induction

Prove by strong induction that for a ∈ A we have $F_a + 2F_{a+1} = F_{a+4} − F_{a+2}.$ $F_a$ is the $a$'th element in the Fibonacci sequence
0
votes
1answer
187 views

Proof by induction involving fibonacci numbers

The Fibonacci numbers are defined as follows: $f_0=0$, $f_1=1$, and $f_n=f_{n−1}+f_{n−2}$ for $n≥2$. Prove each of the following three claims: (i) For each $n≥0$, $f_{3n}$ is even. (ii) For each ...
5
votes
2answers
181 views

Number of bitstrings with $000$ as substring

I have $F_n$ number of bitstrings that have $000$, How would I prove that for $n \ge 4$ , $a_n = a_{n-1} +a_{n-2}+a_{n-3}+ 2^{n-3}$? Now there are many ways to go about this but if I choose starting ...
3
votes
1answer
140 views

Solve Recurrence Equation with Induction

Question: Given the recurrence equation for the recursive Fibonacci sequence program: $T(n) = T(n-1) + T(n-2) + b$ $T(0) = T(1) = a$ Using induction, show that $T(n) \leq f(n)$, where $f(n) = c2^n, ...
0
votes
2answers
114 views

Proving that $fib(n) < (5/3)^n$ for $n \ge 1$ by induction

I know this has been shown before here but no post really answered my question. I had this problem given to me as an induction practice problem and I couldn't solve it without help. When I got the ...
0
votes
1answer
61 views

Proof by Induction for a $f_3 + f_6 + · · · + f_{3n} = \frac{1}{2} (f_{3n+2} - 1)$ [duplicate]

The Fibonacci numbers are defined as follows: $f_0 = 0,\ f_1 = 1$, and for $n ≥ 2,\ f_n = f_{n−1} +f_{n−2}$. Prove that for every positive integer $n$, $$f_3 + f_6 + \ldots + f3_n = \frac{1}{2} ...
0
votes
1answer
385 views

Induction on Fibonacci Sequence and the Golden Ratio

I'm trying to prove $f_n \leq \left(\frac{1 + \sqrt{5}}{2}\right)^{n-1}$ with induction, and I'm stuck in the induction step. Basis: n = 2 $f_{2} \leq \left(\frac{1 + \sqrt{5}}{2}\right)^{2-1} ...
4
votes
2answers
68 views

Fibonacci induction stuck in adding functions together

Using Fibonacci... I am Proving: $$f_3 + f_6 + \cdots + f_{3n} = \frac12(f_{3n+2}-1) $$ I did the assumption of $f_1$ which gave $\mathrm{LHS}=2=\mathrm{RHS}$. For the second part where it is $n+1$ ...
2
votes
1answer
318 views

Exponential lower bound for Fibonacci numbers

Can someone show me how to solve through induction, $F(N) \geq (3/2)^N$ for all $N\geq N_0$, where $F(n)$ is the Fibonacci function and $N_0$ is some positive integer. I know that $N_0$ should be ...
1
vote
1answer
79 views

Proof by induction that fibonacci sequence are coprime

I have a bit difficulty to proofe that two consecutive numbers are coprime. I have the following The property $P(n)$ is the equation $(F_{n+1},F_n)=1$ where F_i the sequence of fibonacci is and $n ...
1
vote
2answers
152 views

Induction proof with Fibonacci numbers

Prove by induction that for Fibonacci numbers from some index $i > 10$ $1.5^i ≤ f_i ≤ 2^i$ Notice! Because Fibonacci number is a sum of 2 previous Fibonacci numbers, in the induction hypothesis ...
0
votes
3answers
244 views

Prove the Number of Additions of Fibonacci Number Algorithm

I am studying for a final exam and I'm having trouble with this question: The following recursive algorithm FIB takes as input an integer $n \ge 0$ and returns the $n$-th Fibonacci number $F_n$: ...
2
votes
4answers
4k views

Help with Induction proof on Fibonacci sequence?

I can't seem to solve this problem. It is: The Fibonacci numbers $F(0), F(1), F(2),\dots $ are defined as follows: $F(0) ::= 0$ $F(1) ::= 1$ $F(n) ::= F(n-1) + F(n-2)\qquad(\forall n \ge 2 $) ...
0
votes
1answer
137 views

Proving Lucas Identity by Induction

I am trying to prove the following identity (I decided to use induction, but if that's not the best way feel free to mention that in the answers): $$L^2_n = 5F^2_n + 4(-1)^n \space\space ...
2
votes
1answer
134 views

Fibonacci Sequence Exercise

I need some help checking the following solution. The Fib sequence is defined by $a_1 = 1, a_2 = 1$ and for all $n\geq 2$, $a_{n+1} = a_n + a_{n-1}$. Thus, the sequence begins: 1, 1, 2, 3, 5, 8, ...
2
votes
3answers
621 views

Using induction to prove a result about the Fibonacci sequence

The Fibonacci sequence $F_0, F_1, F_2,...,$ are defined by the rule $$F_0=0, F_1=1, F_n=F_{n-1}+F_{n-2}$$ Use induction to prove that $F_n\geq2^{0.5n}$ for $n\geq 6$ So far I have done the ...
5
votes
3answers
1k views

Strong Induction Proof: Fibonacci number even if and only if 3 divides index

The Fibonacci sequence is defined recursively by $F_1 = 1, F_2 = 1, \; \& \; F_n = F_{n−1} + F_{n−2} \; \text{ for } n ≥ 3.$ Prove that $2 \mid F_n \iff 3 \mid n.$ Proof by Strong Induction : ...
6
votes
1answer
730 views

Proof by induction on Fibonacci numbers: show that $f_n\mid f_{2n}$

I was studying Mathematical Induction when I came across the following problem: The Fibonacci numbers are the sequence of numbers defined by the linear recurrence equation- $f_n = f_{n-1} + ...
3
votes
2answers
646 views

Inductive proof of the closed formula for the Fibonacci sequence [duplicate]

Fibonacci numbers $f(n)$ are defined recursively: $f(n) = f(n-1) +f(n-2)$ for $n > 2$ and $f(1) = 1$, $f(2) = 1$. They also admit a simple closed form: $$\sqrt 5 f( n ) = \left(\dfrac{1+ \sqrt ...
3
votes
2answers
182 views

Fibonacci using proof by induction: $\sum_{i=1}^{n-2}F_i=F_n-2$

everyone. I have been assigned an induction problem which requires me to use induction with the Fibonacci sequence. The summation states: $$\sum_{i=1}^{n-2}F_i=F_n-2\;,$$ with $F_0=F_1=1$. I ...
2
votes
3answers
147 views

Statement on the Fibonacci sequence

Question: Let $n,m,\in\mathbb{N^*}$ with $n>1$ and let $u_n$ denote the $n$-th term of the Fibonacci sequence, then $$u_{n+m}=u_{n-1}u_m+u_nu_{m+1}$$ I know these theorems: Two consecutive ...
2
votes
3answers
571 views

Strong inductive proof for this inequality using the Fibonacci sequence.

Problem I need to determine for what natural numbers is $2n < F_n$, where $F_n$ is the $n^{th}$ Fibonacci number determined by $F_0 = 0$, $F_1 = 1$ and $F_n = F_{n-1}+F_{n-2}$. I then need to ...
10
votes
4answers
241 views

Fibonacci Cubes: $F_n^3 + F_{n+1}^3 - F_{n-1}^3 =F_{3n}$

Prove $$F_n^3 + F_{n+1}^3 - F_{n-1}^3 =F_{3n}$$ I've tried induction, either its just very long or a neat trick is required in the inductive step but for some odd reason its not working out. ...
2
votes
3answers
712 views

For the Fibonacci numbers, show for all $n$: $F_1^2+F_2^2+\dots+F_n^2=F_nF_{n+1}$

The definition of a Fibonacci number is as follows: $$F_0=0\\F_1=1\\F_n=F_{n-1}+F_{n-2}\text{ for } n\geq 2$$ Prove the given property of the Fibonacci numbers for all n greater than or equal to 1. ...
5
votes
1answer
326 views

What is wrong with my induction proof?

The Fibonacci sequence is defined by $a_1 = 1, a_2 = 1$ and for all $n \ge 2, a_{n+1} = a_n + a_{n-1}$. Thus the sequence begins $$1,1,2,3,5,8,13,21,...$$ prove that for all $n \ge 1, a_n < ...
6
votes
2answers
103 views

Error in Fibonacci recurrence proof by induction?

I'm working on a problem from a number theory book (Number Theory by George E. Andrews - problem 1-1-11). The text reads: Prove: $\displaystyle F_1F_2+F_2F_3+F_3F_4+\ldots+F_{2n-1}F_{2n}=F_{2n}^2$ ...
1
vote
2answers
425 views

proof by induction to demonstrate all even Fibonacci numbers have indices divisible by 3

I am practicing proof by induction, and would like to use induction to prove the following hypothesis about the Fibonacci numbers: $$(\forall n\ge0) \space 0\equiv n\space mod \space 3 \iff 0 \equiv ...
1
vote
2answers
130 views

Induction on the Fibonacci sequence?

Prove by induction that the $i$th Fibonacci number satisfies the equality: $$F_i = \frac {\phi^i - \hat\phi{}^i}{\sqrt5}$$ where $\phi$ is the golden ratio and $\hat\phi$ is its conjugate. ...
7
votes
2answers
141 views

Fiboncacci theorem: Proof by induction

I have the following theorem to prove by induction: $$ F_{n} \cdot F_{n+1} - F_{n-2}\cdot F_{n-1}=F_{2n-1} $$ It is mentioned in my script that the proof should be possible only by using the ...
3
votes
4answers
2k views

Induction Proof: Fibonacci Numbers Identity with Sum of Two Squares

Using induction, how can I show the following identity about the fibonacci numbers? I'm having trouble with simplification when doing the induction step. Identity: $$f_n^2 + f_{n+1}^2 = f_{2n+1}$$ I ...
1
vote
4answers
139 views

Proving that $\alpha^{n-2}\leq F_n\leq \alpha^{n-1}$ for all $n\geq 1$, where $\alpha$ is the golden ratio

I got stuck on this exercise. It is Theorem 1.15 on page 14 of Robbins' Beginning Number Theory, 2nd edition. Theorem 1.15. $\alpha^{n-2}\leq F_n\leq \alpha^{n-1}$ for all $n\geq 1$. Proof: ...
2
votes
1answer
222 views

Simple Fibonacci / Lucas Numbers Relationship

Prove the identity by induction: $$ F_{2n} = F_n L_n, $$ where $F_n$ and $L_n$ are the $n^{th}$ Fibonacci and Lucas number, respectively. I have an answer but am not happy with it since it doesn't ...
4
votes
3answers
243 views

Why doesn't this induction “proof ”show $f_n = (\phi)^n + (1-\phi)^n$?

Here, $\phi$ is the golden ratio and $f_n$ is the $n^{th}$ Fibonacci number. The formula I'm using is actually the closed form of the Lucas numbers. Let $n = 1$. Then $f_n = 1$ and $\phi + 1 - \phi ...
3
votes
2answers
572 views

Induction Proof: Formula for Fibonacci Numbers as Odd and Even Piecewise Function

How can we prove by induction the following? $ F_{n+1} = \left\{ \begin{array}{l l} F_{n/2}^2+F_{(n+2)/2}^2 & \quad \text{if $n$ is even}\\ ...
3
votes
1answer
1k views

Induction Proof: Formula for Sum of n Fibonacci Numbers

I am stuck though on the way to prove this statement of fibonacci numbers by induction : my steps: definition: $F_{0}:=0, F_{1}:=1 $ and $F_{n}:=F_{n-1}+F_{n-2}$ The Hypothesis is: $\sum_{i=0}^{n} ...
4
votes
1answer
276 views

prove that $\operatorname{fib}(n)<{(5/3)}^n$

I am trying to prove that $$ \operatorname{fib}(n)<\left(\frac{5}{3}\right)^n $$ where $\operatorname{fib}(n)$ is the $n^{th}$ fibonacci number. For a proof I used induction, as we know ...